Decrease in salivary cortisol levels after glucocorticoid dose reduction in patients with adrenal insufficiency: A prospective proof‐of‐concept study. (24th October 2017) - Ceccato, Filippo; Barbot, Mattia; Lizzul, Laura; Selmin, Elisa; Saller, Alois; Albiger, Nora; Betterle, Corrado; Boscaro, Marco; Scaroni, Carla
Summary: Background and aim: Patients with adrenal insufficiency (AI) require lifelong glucocorticoid (GC) replacement therapy. Cortisol measurement in saliva is increasingly being used: we assessed salivary cortisol rhythm in outpatients with AI, to provide new insights regarding the management of GC treatment. Materials and methods: Nineteen AI outpatients collected six saliva samples from awakening (F a, before taking the morning GC therapy), during the day (F 1.5 h, F 6 h before the afternoon GC dose, F 8.5 h, F 12 h ) until bedtime (F b ). We measured daily cortisol exposure by calculating the area under the curve (AUC Fa→Fb ). Saliva samples were collected at baseline and one year after GG dose reduction (by at least 5 mg of hydrocortisone). Results: Hydrocortisone equivalents decreased from median 25 mg/d (baseline, interquartile range IQR 20‐27.5) to 15 mg/d (IQR 15‐20, P < .01). As expected, we observed a reduction in both daily cortisol exposure (AUC Fa→Fb 23 982 nmol·h/L, IQR 12 635‐45 369, to 14 689 nmol·h/L, IQR 7168‐25 378, P < .001) and salivary cortisol levels at F 6 h (24.8 nmol/L, IQR 20.1‐35.7, to 21 nmol/L, IQR 8.7‐29.2, P < .05) and F b (8.7 nmol/L, IQR 3.4‐20.2, to 3.7 nmol/L, IQR 3.0‐5.8, P < .05). None of the patients developed signs or symptoms consistent with AI after GC reduction. Median diastolic blood pressure (DPB) values fell from baseline to the end of follow‐up (87.5 mm Hg, IQR 80‐90, to 80 mm Hg, IQR 80‐85, P < .05). The AUC Fa→Fb of patients at baseline was above the reference value (90th percentile of controls) in 12 patients (60%); after the dosage reduction, 30% of patients normalized their daily cortisol exposure (AUC Fa→Fb ). Conclusions: The reduction in GC treatment in patients with AI resulted in better control of daily cortisol rhythm, measured with salivary cortisol, and in an improvement of DPB. Further studies are needed to ascertain if salivary cortisol could be used as a biomarker to manage GC replacement therapy.